Examining the roles of students' beliefs and security concerns for using smartwatches in higher education. Issue 4 (16th September 2020) - Al-Emran, Mostafa; Granić, Andrina; Al-Sharafi, Mohammed A.; Ameen, Nisreen; Sarrab, Mohamed
Abstract : Purpose: Despite the increased use of wearables in education, little attention has been paid to why some students are more likely to adopt smartwatches than others. The question of what impacts the adoption of smartwatches in educational activities is still neglected. In addition, the question of how security determinants can affect the adoption of smartwatches by students has not been addressed yet. Hence, this study aims to develop a theoretical model by integrating the technology acceptance model (TAM) and protection motivation theory (PMT) to study students' adoption of smartwatches for educational purposes. Design/methodology/approach: Questionnaires were distributed to university students in Malaysia. A total of 679 valid responses were collected. The collected data were analyzed using partial least squares-structural equation modeling (PLS-SEM). Findings: The results of data analysis provide support for the proposed model. Furthermore, the findings indicated that perceived vulnerability, self-efficacy, response efficacy, response cost, ease of use and perceived usefulness have significant effects on students' behavioral intention to use smartwatches for educational purposes. In addition, perceived ease of use of smartwatches for educational purposes helps students to realize the benefits of this technology. Originality/value: This is an original study that develops a new holistic theoretical model by combining the PMT and TAM to study the effects of ease of use, usefulness and security-related factors on the adoption of smartwatches for educational purposes. The study offers practical implications for universities and higher education institutions to improve students' learning experiences to ensure their sustainability using new and innovative ways by exploiting new technologies such as smartwatches.